SOCIAL POLICY PRIORITIES OF THE CHINESE MARKET REFORMS - Антоненко, Леонид Анисимович; Цюйши, Ван (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
The author’s proposals on using the social strategic priorities from the experience of the Chinese market reforms in the process of the normative legal framework ofUkraineimproving during the implementation of the main positions of the “Strategy-2020”are substantiated in the article. Thus the author has used the rarely found inUkraineworks by Chinese authors. The character of the cause and effect relations of the Chinese reforms results and their instruments to improve the people's living standards is covered in them from the different positions. The author’s scientific novelty of the held research lies in the fact that the made generalizations and proposals enlarge the existing in the economic science views on the social priorities of the market transformations in the countries with the centralized state planning system. The preservation of the long-term state planning at the sphere of private property extension is shown.The stages of reforming are identified. The first stage (2000-2010) is characterized by launching the realization of the course in accordance with the perspective of development on the gross domestic product (GDP) doubling.At the second stage (2011-2030) it is scheduled the GDP per capita doubling, a mature system of the market socialist economy creating and an average income at the level of provision achieving.At the third stage (2031-2049), that is to the 100th anniversary of the People’s Republic ofChinaformation, it is supposed to get the GDP per capita re-doubling. This will be achieved by modernization of industry, agriculture, science and technology, defense complex to ensure the living standards of the moderately developed countries.At the fourth stage (2050-2079), that is to the 100th anniversary since the beginning of the policy of economic reforms and strengthening of openness to the outside world, the next GDP per capita doubling is planning. During this period the full reorganization of the territory and environment is expected. On this basis the consumption will be at the level of the overall prosperity.At the fifth stage (2080-2100) it is supposed that until the end of the centuryChinawill overtake the advanced countries on the level of the economic development. It means that the life of all people will be at the level of comprehensive and full prosperity.This is the essence of the realization of the long-term priorities of the development of China. In the process China will focus on the social and economic standards and UN recommendations.